Relationship between bicultural identity and psychological well-being among American and Japanese older adults - Ayano Yamaguchi; Min-Sun Kim; Atsushi Oshio; Satoshi Akutsu (Health Psychology Open, 2016)
In a large national sample of American and Japanese older adults, this study investigated how bicultural identity affects perception of health and well-being in 11 individual psychological variables (i.e. positive well-being: self-esteem, optimism, subjective well-being Japanese equivalent, gratitude, Positive and Negative Affect Schedule–positive adjectives, and satisfaction with life; negative well-being: depression, pessimism, social anxiety, Positive and Negative Affect Schedule–negative adjectives, and perceived stress). This sample consisted of 1248 Americans from the Midlife in the United States survey, 2004–2006, and 380 Japanese from the Midlife in Japan survey in Tokyo, Japan, 2008–2010. Results showed that bicultural individuals (having both highly independent and interdependent self-construals) in both countries tend to exhibit higher scores across most perceived health and well-being measures when compared to other groups (i.e. marginal, interdependent, and independent). Cultural-specific aspects of self-construal, health, and well-being are explained to support the findings. Discussion of these findings and their implications is also provided.